A note on the variation in shape of linear rogue waves in the ocean - Adcock, T; Draper, S (Society for Underwater Technology, 2015)
The average shape of large waves in the open ocean made up of linear waves with random phase is given by 'NewWave' defined by the auto-correlation function of the wave spectrum. In this paper, we confirm this result for realistic directionally spread sea-states but show that there is a considerable variation in shape of rogue waves. Practical implications are discussed.